PENGAWASAN PEREDARAN OBAT TRADISIONAL DI KOTA PEKANBARU - Lidia Murniati Silitonga; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Supervision of traditional medicines needs to be carried out by the Regional Government and implemented properly so that it protects the rights of consumers. However, there are still problems in monitoring traditional medicine, so there are still illegal traditional medicines on the market. The purpose of this study was to determine and analyze the Supervision of the Center for Drug and Food Supervision (BBPOM) in the Distribution of Traditional Medicines in Pekanbaru City since there are still many drugs and food products made from chemical drugs (BKO), illegal, and expired circulating in the community. The theory used in this study is the supervision theory of Efendi. The research method used is qualitative with qualitative descriptive techniques. The results of this study are that the supervision conducted by the Center for Drug and Food Supervisors in Pekanbaru City has not been optimal, due to the minimal number of supervisory human resources, lack of funds / funds and the socialization of traditional medicines. The advice given is to make recommendations for adding more employees to the central BPOM staffing bureau, the use of social media in socializing traditional medicine.  Keywords: BPOM, Supervision, Distribution, Traditional Medicine.